2011
DOI: 10.1111/j.1540-8167.2010.01992.x
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Cardiac Autonomic Stimulation Induces Pulmonary Vein Ectopy and Triggers Atrial Fibrillation in Humans

Abstract: This study has demonstrated a direct link between activation of the intrinsic cardiac autonomic nervous system and pulmonary vein ectopy in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 42 publications
1
58
0
Order By: Relevance
“…Pacing frequency was set at 20 Hz, pacing output at 20 mA with a pulse duration of 2 ms, based on earlier research. 13,[16][17][18][19] Stimulation duration was 60 s or shorter when SBP increased beyond 180 mm Hg. We waited for the BP to return to baseline values before proceeding to the next stimulation site.…”
Section: Methodsmentioning
confidence: 99%
“…Pacing frequency was set at 20 Hz, pacing output at 20 mA with a pulse duration of 2 ms, based on earlier research. 13,[16][17][18][19] Stimulation duration was 60 s or shorter when SBP increased beyond 180 mm Hg. We waited for the BP to return to baseline values before proceeding to the next stimulation site.…”
Section: Methodsmentioning
confidence: 99%
“…Approximately 50% of GP sites that produce ectopic triggering by sync-HFS do not produce an AV nodal response by cont-HFS; however, 90% of sites with an AV nodal response will trigger ectopics. 1 Canine studies suggest that the network has a common pathway into the AV node via the right lower (RL) GP (RLGP) and ablation here abolishes the AV nodal effects from other left atrial (LA) GP sites. 7 Similarly, a common input to the SA node via the right upper (RU) GP (RUGP) exists in dogs, whereby ablation at the RUGP significantly attenuates sinus rate slowing in response to GP stimulation.…”
Section: Editorial See P 458 Clinical Perspective On P 640mentioning
confidence: 99%
“…1,2 In canine studies, epicardial ganglionated plexi (GP) ablation was able to abolish both AF induction and maintenance completely. 3 Although clinical AF ablation has focused on pulmonary vein isolation (PVI), there is a high PV electric reconnection rate even in patients who remain symptomfree.…”
mentioning
confidence: 99%
“…79,80 GP connect the extrinsic autonomic nervous system (brain, spinal cord, and ganglia/nerves outside of the heart) to the intrinsic autonomic nervous system within the heart, and are important mediators by which autonomic stimuli influence AF and other arrhythmias. 81 Autonomic signals to the heart via GP exert important electrophysiological effects including altering atrial refractory periods, 81,82 increasing the frequency of triggered atrial premature beats that can subsequently initiate AF, 83 and increasing the vulnerability of atrial tissue to the induction of AF. 81,84,85 Animal studies have demonstrated that stimulation of GP located around the pulmonary veins can reduce the number of atrial extrastimuli required to initiate AF, and that neuronal/autonomic blockade with drugs or GP ablation can prevent AF induction.…”
Section: The Influence Of the Autonomic Nervous System And Ganglionatmentioning
confidence: 99%